Agricultural research in Africa: Investing in future harvests - Lynam, John K.; Beintema, Nienke M.; Roseboom, Johannes; Badiane, Ousmane (International Food Policy Research Institute, 2016)
This book—prepared by Agricultural Science and Technology Indicators (ASTI), which is led by IFPRI—offers a comprehensive perspective on the evolution, current status, and future goals of agricultural research and development in Africa, including analyses of the complex underlying issues and challenges involved, as well as insights into how they might be overcome. Agriculture in Africa south of the Sahara is at a prospective tipping point. Growth has accelerated in the past decade, but is unsustainable given increasing use of finite resources. The yield gap in African agriculture is significant, and scenarios on feeding the world’s population into the future highlight the need for Africa to expand its agricultural production. Agricultural Research in Africa: Investing in Future Harvests discusses the need to shift to a growth path based on increased productivity—as in the rest of the developing world— which is essential if Africa is to increase rural incomes and compete in both domestic and international markets. Such a shift ultimately requires building on evolving improvements that collectively translate to deepening rural innovation capacity.